Возвращение "Серых волков" : Консервативная партия в политической жизни Турции (1983-1985) - Сафрастян, Рубен («Զանգակ - 97»)
In Turkey it is accepted lo call the members of the right-wing radical extremist pan -Turkist parties and organizations as "grey wolves". They are closely related to each other and they have their paramilitary groups and have deeply penetrated into all the layers of Turkish society and State apparatus. Actually the "grey wolves' are а well organized hierarchical network operating within lhc country and abroad. The leadership of lhe Party of Nationalistic Action (PNA) - the biggest political party representing the trend of pan-Turkism in the politics of the country for forty years, controls this network.
Keywords: История; Политика; Турция